FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI PANGAN SUMBER KARBOHIDRAT DI PROVINSI SUMATERA BARAT - Ramadanus Ramadanus; Suardi Tarumun; Elinur Elinur (DINAMIKA PERTANIAN, 2013)
This study aims to determine the factors affecting food consumption as carbohydrate sources in the province of West Sumatra. The data used is the data for Socio-Economic Survey of 2011 which is sourced from Statistics of West Sumatra Province. To see the factors that affect food consumption models built carbohydrate Almost Ideal Demand System (AIDS) were analyzed by the method of Seemingly Unrelated Regresion (SUR). Results of the study showed that the factors that influence food consumption of carbohydrate source is the price of the commodity itself, other commodity prices, education, household income, household mother, spending on consumption and region of residence. Response to price themselves commodities carbohydrate food sources are negative which indicates that all categories of commodities including normal goods. Shows the cross-price response substitution and complementary relationships between each commodity, all revenue Response carbohydrate food commodities is positive, which means that all commodities including staple goods. Increase residents' income to reduce the negative impact of rising food prices carbohydrate source. The strong response to changes in the price of rice to other commodities indicates that policy interventions are still needed in the field of rice. Tubers for food need to be improved so that the availability of these more stable commodity prices in the market because the requested amount is influenced by the price.